ACTIVE AGING AMONG THE ELDERLY AND ITS ECONOMIC AND SOCIAL CONSEQUENCES IN BULGARIA - Vazova, Tanya; Vazov, Radostin; Radev, Vilislav (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study investigates the multidimensional factors contributing to active ageing among older adults in Bulgaria and examines its broader implications for the country’s social and economic development. Moving beyond traditional notions of ageing as a period of dependency and withdrawal, active ageing is framed here as a dynamic process that empowers older individuals to remain healthy, socially engaged, and economically productive. The novelty of this research lies in its integrative approach, combining sociological, economic, and technological perspectives to assess how ageing can be redefined as an opportunity rather than a burden. By evaluating key determinants—such as physical and mental health, intergenerational relationships, social integration, economic security, lifelong learning, and digital inclusion—the study provides a holistic understanding of what enables active participation in society later in life. Particular emphasis is placed on Bulgaria’s unique demographic context, marked by accelerated population ageing, a declining working-age population, and high rates of youth outmigration. These challenges intensify the need for effective policies and community-based interventions that promote independence, dignity, and lifelong contribution. The analysis highlights that active ageing is not only shaped by personal capacity but also by the accessibility of public services, the inclusiveness of social networks, and the digital readiness of the elderly population. Furthermore, the study underscores how societal attitudes toward older people influence their opportunities for social inclusion and economic engagement. By identifying enablers and barriers, this research offers actionable insights for policymakers aiming to strengthen Bulgaria’s resilience in the face of demographic change through inclusive, age-positive development strategies.